Giant Bronchogenic Cyst with Minimal Clinical Presentation - Parikesit, Petra Gusti; Ramba, Aldheavany Ratu; Tabuni, Carolus Boromeus; Dewi, Kristin Purnama (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Bronchogenic cysts are rare congenital malformations of the respiratory tract, typically presenting as cystic structures filled with fluid or air. Although generally detected in childhood, some cases remain asymptomatic and are discovered incidentally in adulthood. This case report aims to describe the clinical findings, diagnostic process, and management of a giant bronchogenic cyst detected incidentally in an adult patient. This study used a case report approach. A 56-year-old female patient underwent routine health screening in which a thoracic abnormality was detected. Diagnostic evaluation included chest radiography, thoracic computed tomography (CT) scan, and CT-guided fine needle aspiration biopsy with cytological examination. Chest radiography revealed a large mass in the paratracheal region without mediastinal shift. Further evaluation with thoracic CT scan confirmed a massive hypodense cystic lesion measuring 14.8 × 9.0 × 17.0 cm in the left hemithorax, extending to the left paracardial region and causing partial collapse of the left lung. CT-guided fine needle aspiration produced clear fluid, and cytological analysis showed no evidence of malignancy, supporting the diagnosis of a benign bronchogenic cyst. The patient subsequently underwent surgical resection. In conclusion, Giant bronchogenic cysts may remain asymptomatic and be detected incidentally. Imaging modalities combined with histopathological confirmation play a crucial role in establishing the diagnosis. Surgical resection is the definitive treatment to prevent potential complications and possible malignant transformation, even in asymptomatic cases.Keywords: bronchogenic cyst; congenital lung cyst; case report